What is the First Output OXFAM Would Like From Its Partnership With CCAFS? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Kate Raworth - Senior Researcher at OXFAM. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya